Biology and parasitic potential of Doryctobracon areolatus on Anastrepha fraterculus larvae - Nunes, Adrise Medeiros; Nava, Dori Edson; Müller, Fernanda Appel; Gonçalves, Rafael da Silva; Garcia, Mauro Silveira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to study the biology and parasitic potential of Doryctobracon areolatus on larvae of Anastrepha fraterculus. The egg–adult period, the sex ratio, the longevity, the pupal viability, and the parasitism rate of D. areolatus were determined in laboratory, using A. fraterculus as host. The parasitoid development from oviposition to adult emergence required 25.00±1.70 days, the sex ratio was 0.62±0.09, and the mean longevity was 16.36±3.62 days for males and 10.24±1.71 days for females. The mean parasitism rate was 53.50±8.93%, varying from 41.60 to 68.60%, which shows the potential of this parasitoid for biological control of A. fraterculus.